Management of Emergency Services in Some Selected Upazila Health Complexes - Khan, Mohammad Kamruzzaman; Rahman, Zahidur; Kaiser, Fazlur Rahim; Ferdous, Jannatul (Medicine Today, 2012)
Medicine Today 2010 Volume 22 Number 02 Page 88-91 DOI: http://dx.doi.org/10.3329/medtoday.v22i2.12441